Képpé vált szöveg, szöveggé vált kép - Szegedy-Maszák, Mihály (Studia Litteraria, 2013)
How can an image be turned into a text? This question has preoccupied artists and art experts for thousands of years. There seems to be three potential intersections of spectacle and verbal utterance. First, description has received a substantial amount of critical attention, which of course does not mean that there are no other relevant phenomena requiring further study. Second, the interrelationship of written, moulded or painted portraits also makes it worthwhile to explore the connections between portrait painting and biography. The third kind of encounter between text and image is the narrative. Is it possible at all to narrate a story in the form of image(s)? The answer is by far not as evident as certain critics argue, since a narrative does not only presuppose a plot but a narrator as well, that is, a linguistic construct. It is thus especially reasonable to speak of a pictorial narrative where the images are to represent subsequent phases of the story. The paper aims to examine these issues on the basis of relevant examples, such as texts by Virginia Woolf and Miklós Bánffy.